O processo de inclusão do indivíduo cadeirante em aulas de educação física: um olhar da comunidade escolar - FERREIRA, Danielen Costa (2022)
The interest in individuals using wheelchairs was based on the adapted Physical Education (PE) discipline. Wheelchair children are able to acquire a repertoire of knowledge that is taught to them from the moment they are stimulated, especially with regard to motor experiences. In this sense, the aim of our study was to investigate the challenges and possibilities for the role of the PE teacher in the process of inclusion of students using a wheelchair. The research has a qualitative approach and was developed at the public kindergarten and elementary education. The subjects were: school management, special education technician, regular education teacher, itinerant PE teacher, parents/guardians of the student and 2 classmates (3rd grade students). Volunteers answered a semi-structured questionnaire with questions that addressed the inclusion of wheelchair users in the school. Our results indicated that the school institution should be effectively more oriented towards the particularities presented by the students than towards the needs of society. In addition, schools need to value diversity and promote equity in their learning, ensuring that their collective and individual needs are met, so that their role in individual training enables the construction of a culture of respect for diversity and combating inequalities. Thus, our conclusion enabled a better understanding of the issue of inclusion of wheelchair users during their participation in the teaching-learning process, especially in PE classes. However, institutionalized spaces for the education of children still need adjustments, both physical spaces and spaces for training specialized professionals to work with this population.